2022
DOI: 10.1172/jci153943
|View full text |Cite
|
Sign up to set email alerts
|

SCF-SKP2 E3 ubiquitin ligase links mTORC1/ER stress/ISR with YAP activation in murine renal cystogenesis

Abstract: The Hippo pathway nuclear effector Yes-associated protein 1 (YAP) potentiates the progression of polycystic kidney disease (PKD) arising from ciliopathies. The mechanisms underlying the increase in YAP expression and transcriptional activity in PKD remain obscure. We observed that in kidneys from mice with juvenile cystic kidney (jck) ciliopathy, the aberrant hyperactivity of mechanistic target of rapamycin complex 1 (mTORC1) driven by ERK1/2 and PI3K/AKT cascades induced endoplasmic reticulum (ER) proteotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…TUDCA appears to have effects beyond those of a chemical chaperone(2628) Our differential expression data comparing the 4 month Col4α3 −/− and Col4α3 −/− -T transcriptomes suggest that TUDCA also increases expression of genes that suppress Ras-MAPK, tyrosine kinase, and FGF signaling as well as TGF-β-induced epithelial-mesenchymal transformation, and actin remodeling ( Figure 4 ). These effects of TUDCA may contribute to its improvement in podocyte viability and suppression of tubulo-interstitial injury in Alport nephropathy.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…TUDCA appears to have effects beyond those of a chemical chaperone(2628) Our differential expression data comparing the 4 month Col4α3 −/− and Col4α3 −/− -T transcriptomes suggest that TUDCA also increases expression of genes that suppress Ras-MAPK, tyrosine kinase, and FGF signaling as well as TGF-β-induced epithelial-mesenchymal transformation, and actin remodeling ( Figure 4 ). These effects of TUDCA may contribute to its improvement in podocyte viability and suppression of tubulo-interstitial injury in Alport nephropathy.…”
Section: Discussionmentioning
confidence: 97%
“…TUDCA suppresses the effects of UPR activation, and in these studies preserves glomerular biophysical properties, reduces podocyte loss, tubulo-interstitial fibrosis and inflammation, proteinuria, and loss of excretory function. All of these beneficial effects may derive from improved podocyte function, but TUDCA may also have additional effects including suppression of inflammation (28, 59, 60). We find that TUDCA increases the expression of mRNAs that could suppress fibrosis, cell migration or inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of ISR, mainly the UPR branch, in the context of cystic kidney disorders is still debated. Indeed, it has been described that activation of the PERK-dependent branch and activation of the downstream ATF4 transcriptional program contributes to establishment of juvenile cystic kidney ciliopathy (Panda et al , 2022). On the other hand, Fedeles et al demonstrated that activation of the UPR pathway plays a protective role against cyst formation, but that the pathway itself is not deregulated in those kidneys (Fedeles et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Jck mouse model results from a double point mutation in the Nek8 gene [18]. While mutations in this gene are responsible for nephronophthisis in humans [40], mutant mice display features that recapitulate an ADPKD phenotype [41,42]. The disease progresses relatively rapidly to end stage renal disease at 4 months.…”
Section: Discussionmentioning
confidence: 99%